EFEK KOMBINASI ARTEMISININ DAN N-acetylcysteineTERHADAP KADAR Malondialdehyde(MDA) OTAK DAN PARU MENCIT GALUR Balb/c YANG DIINFEKSI Plasmodium berghei - Fitri, Loeki Enggar; Iskandar, Agustin; Permatasari, Nur; Gunawan, Joko Agus; Indrawan, Khadafi (Jurnal Kedokteran Brawijaya, 2008)
Cerebral and lung damage during malaria infection is believed to be caused by free radicals activitiesthat are produced during immunology process. The free radicals react with lipid component of cellular membrane which generates malondialdehyde (MDA) as its end-product. The aim of the research was to determine whether combination of artemisinin and NAC was moreeffective in decreasing cerebral and lung MDA level compared to artemisinin mono-therapy . The researchwas post-test-control-only design using 5 groups consisted of group A (negative control group), group B mice which infected with P.berghei without therapy (positive control group), group C mice which infected with P.berghei and received artemisinin mono-therapy (0.04 mg/g BW for 7 days), group D mice which infected with P.berghei and received artemisinin in combination with NAC (1 mg/g BW for 7 days) and group E mice which infected with P.berghei and received artemisinin in combination with NAC (1 mg/g BW for 3 days and tapered into ½ mg/g BW for 4 days). On the 3rd, 5th,and 7thday, 3 mice from each group were scarified and assayed for MDA level. On the 3rd day, a decreasing trend of cerebral and lung MDA level wasobserved on all treatment groups. On the 5thday, a decreasing trend of cerebral and lung MDA level wasobserved in group that received artemisinin and NAC whereas group’s that received artemisinin mono-therapy increased. Cerebral and lung MDA level of groupthat received artemisinin mono-therapy was significantly different with group that received combination of artemisinin and NAC in constant dose (p = 0.014) and with group that received combination artemisinin  and NAC in tapering dose (p = 0.004).